Downregulation of LINC00638 contributes to the pathogenesis of rheumatoid arthritis-associated interstitial lung disease via inhibiting the Nrf2/ARE signaling pathway - Zhuojun LIAO; Naiwang TANG; Jiahui CHEN; Xueying SUN; Jiamin LU; Qin WU; Ronghuan YU; Ying ZHOU (Zhongguo Linchuang Yixue, 2025)
ObjectiveTo identify long non-coding RNA (lncRNA) associated with rheumatoid arthritis-associated interstitial lung disease (RA-ILD) and investigate their mechanisms. MethodsPeripheral blood samples were collected from RA-ILD patients (n＝3), RA patients without lung involvement (n＝3), and healthy controls (n＝3). Next-generation sequencing was performed to screen differentially expressed lncRNA. A human fibrotic lung cell model was established by inducing the MRC-5 cell line with transforming growth factor-β (TGF-β). Following siRNA-mediated knockdown of target genes, changes in inflammatory and oxidative stress-related genes were analyzed via real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). Western blotting and dual-luciferase reporter (DLR) assays were used to validate protein expression, ubiquitination levels, and nuclear translocation of oxidative stress regulators, and antioxidant response element (ARE) transcriptional activity. Rescue experiments were conducted to confirm the role of target lncRNA in oxidative stress and inflammation in fibrotic lung cells. Results High-throughput sequencing revealed significant downregulation of LINC00638 in RA-ILD patients. Knockdown of LINC00638 markedly reduced transcriptional levels of interleukin (IL)-4, nuclear factor erythroid-2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and superoxide dismutase 2 (SOD2), while increasing IL-6, IL-1β, interferon-γ (IFN-γ), and reactive oxygen species (ROS) levels. Furthermore, LINC00638 knockdown decreased Nrf2 protein expression, increased its ubiquitination, reduced nuclear translocation, and suppressed ARE transcriptional activity. In MRC-5 cells, LINC00638 knockdown combined with N-acetylcysteine treatment restored Nrf2 and HO-1 levels while reducing IL-6 expression. ConclusionsLINC00638 suppresses inflammatory responses in RA-ILD by activating the Nrf2/ARE antioxidant signaling pathway, suggesting its potential as a therapeutic target for diagnosis and treatment.